1998
DOI: 10.1046/j.1365-277x.1998.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of point‐of‐choice nutrition labelling schemes in the workplace, public eating places and universities

Abstract: Background: Nutrition labelling schemes at the point‐of‐choice allow opportunity for behaviour change by modifying the environment. In the workplace they provide a particularly good opportunity to expose employees repeatedly to healthier food choices. The Heartbeat Award scheme (HBA) is an example of such a scheme and was launched in England in 1990 by the Health Education Authority. Method: Twenty point‐of‐choice labelling schemes are reviewed in the workplace, public eating places and universities. We outlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…Secondly, nutrition information alone is not enough to change food choices and dietary intake. Studies have shown that an even more important moderator than knowledge is personal motivation when changing eating habits, together with interventions that target self-efficacy [95][96][97]. Leading on to the third argument, gamification is not a game as such, but a design process involving motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, nutrition information alone is not enough to change food choices and dietary intake. Studies have shown that an even more important moderator than knowledge is personal motivation when changing eating habits, together with interventions that target self-efficacy [95][96][97]. Leading on to the third argument, gamification is not a game as such, but a design process involving motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Modifications to the environment such as posting nutrition information in university canteens might not cause an immediate dietary change [10]. Consumer behaviour and information processing models posit that communication and information efforts, if being attended to and properly processed, move individuals through a sequence of hierarchical stages, often referred to as a “hierarchy of effects” [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, direct comparability of nutrient information across options has been shown to induce more advantageous product selections 13,17 , and there is evidence suggesting that nutrition labeling schemes may be more effective when they are better adapted to a target audience or when they employ simple messages that promote taste as well as healthiness 18 . Given specific behavioral recommendations, subsequent decision-making is evaluated more favorably according to both consumers' own judgments and expert standards 19 .…”
Section: Discussionmentioning
confidence: 99%